LENGTH GROUP AND SPECIES-SPECIFIC GROWTH RESPONSES OF CARNIVOROUS FISH UNDER CHRONIC EXPOSURE OF METALS MIXTURE - Z. Bashir; M. Javed; S. Abbas3 (Journal of Animal and Plant Sciences, 2021)
The present research study was conducted to determine the effect of sub-lethal (1/3rd of LC50) concentrations of heavy metals mixture (Cd+Cr+Co+Cu+Ni) on the growth performance of two carnivorous fish species viz. Channa marulius and Mystus seenghala, under laboratory conditions. The statistical differences among various growth parameters of the treated and control fish were analyzed by employing the Factorial experiments under RCBD and Tukey’s/Student Newman-Keul tests. The three length groups (50, 100 and 150 mm) of each fish species were divided into two groups i.e., treated and control. For a period of 120 days, each group of fish species was exposed to Cd+Cr+Co+Cu+Ni mixture, separately and growth of the treated fish was compared with that of the control fish group. The fish growth trials were conducted, by selecting a group (n=10) of each length group and fish species. The experiments were conducted with three replications for each exposure concentration, separately. The growth performance of three length groups (50, 100 and 150 mm) of metals mixture treated and control fish groups was monitored in terms of increase/decrease in average wet weights (g) and total lengths (mm), feed intake (g), condition factor and feed conversion ratio. The data on all the growth variables of fish were collected, on weekly basis and analyzed statistically. The Results showed that all the three (50, 100 and 150 mm) length groups of Cd+Cr+Co+Cu+Ni mixture treated fish revealed significantly reduced growth, in terms of increase in average wet weights, total lengths and feed intake as compared to the three length groups of control fish. However, the treated fish showed significantly higher values of condition factor (K) as compared to the control fish. Regarding overall means, the 150 mm fish showed significantly better average wet weight and total length increments, and feed intake while lower FCR as compared to 100- and 50-mm length groups. The 50 mm fish exhibited significantly better K value than that of 100- and 150-mm length groups of fish. During chronic Cd+Cr+Co+Cu+Ni mixture exposure, Channa marulius exhibited significantly (p<0.01) higher average wet weight and total length increments, feed intake and condition factor while lower FCR as compared to Mystus seenghala.
Keywords: Channa marulius; Mystus seenghala; length groups; metals mixture; chronic exposure; growth